2018
DOI: 10.18805/lr-395
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical properties of Cicer spp reveal distinction between wild and cultivated chickpea genotypes

Abstract: Chickpea (Cicer arietinum L.) is the third most important legumes after beans and peas in the world. Turkey is one of the main chickpea producing countries but the yield is not within the expected quantity considering cultivated area. Breeding chickpea varieties requires well-characterized wild Cicer spp progenitors including C. reticulatum, C. echinospermum, C. bijugum and C. pinnatifidum that exhibit sympatric distribution in the Southeastern Anatolia region of Turkey. This study contributes to the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Leguminous crops are an integral component of different cropping systems established around the world. Chickpea (Cicer arietinum L.) is the third most important crop of these cropping systems after peas (Pisum sativum L.) and beans (Phaseolus vulgaris L.) [23]. Chickpea is nutritionally rich and can substitute meat for protein intake in humans [24].…”
Section: Introductionmentioning
confidence: 99%
“…Leguminous crops are an integral component of different cropping systems established around the world. Chickpea (Cicer arietinum L.) is the third most important crop of these cropping systems after peas (Pisum sativum L.) and beans (Phaseolus vulgaris L.) [23]. Chickpea is nutritionally rich and can substitute meat for protein intake in humans [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, molecular characterization studies on ascochyta blight in different chickpea species have been reported in various studies (Phan et al 2002;Cho et al 2005;Bahr et al 2016;Baite et al 2017;Kumar et al 2020) including in Türkiye (Bayraktar et al 2007). However, there were limited studies on the blight in wild Cicer species in the world and even in Türkiye (Abbo et al 2007;Peever et al 2007;Frenkel et al 2010;Kafadar et al 2019;von Wettberg et al 2018). Also, a first report on ascochyta blight of C. montbretii was studied in Bulgaria by Kaiser et al (1998).…”
Section: Resultsmentioning
confidence: 99%
“…Three pathotypes, pathotype I (the least virulent), pathotype II Research Article 8 (moderately virulent) and pathotype III (the most virulent) were determined but later the fourth pathotype (high degree of virulent) has already been reported (Turkkan et al 2008;Nalcaci et al 2021). It has not only been found in the cultivated chickpea, but also reported in wild species (Frenkel et al 2010;Kafadar et al 2019;von Wettberg et al 2018). Molecular determination of ascochyta blight of chickpea is essential for effective disease control and efficient chickpea resistance breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…components. Therefore, plant based food sources are more common than animal based types and cheaper (Topalak and Ceyhan 2015;Kahraman 2017;Kafadar et al, 2019). According to the long term data of FAO (Anonymous 2019), although legumes take second place in the production of field crops, consumption by per person is quite low.…”
Section: Intrоduсtiоnmentioning
confidence: 99%